Homogenizing process of lithium ion battery composite positive electrode slurry and application thereof

Through the process method of step-by-step pulping and composite homogenization of dry and wet methods, the problems of long homogenization time and high cost in the preparation of the positive electrode slurry of lithium-ion batteries are solved, and the high uniformity of the slurry and electrode performance are improved.

CN119542359APending Publication Date: 2025-02-28HUADING GUOLIAN SICHUAN POWER BATTERY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411717360.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode slurry preparation process has problems such as long homogenization time and high cost, and it is difficult to effectively improve the uniformity of the slurry and electrode performance.

Method used

The process of step-by-step pulping and composite homogenization is adopted by dry and wet method. Through high-speed mixing and stirring, the positive electrode material, conductive agent, binder and lithium supplement agent are gradually added, and solvent is added in the form of spray to perform multi-stage dispersion and ultrasonic foam removal, and the viscosity and solid content are adjusted.

Benefits of technology

The homogenization time is significantly shortened, the uniformity and electrode performance of the slurry are improved, the electrode impedance is reduced, the low temperature and cycling performance is improved, and the solvent usage and production cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion batteries, in particular to a homogenizing process and application of lithium ion battery composite positive electrode slurry, and the homogenizing process method comprises the following steps: in the high-speed mixing and stirring process, adding a positive electrode material, a conductive agent, a lithium supplement agent, a binder and the like into a first slurry system and a second slurry system in sequence according to a proportion; mixing by a pipeline high-speed mixer, conveying into a stirring tank, adding partial solvent, conductive slurry, dispersing agent and the like in a spraying manner to prepare primary first slurry and secondary slurry of the positive electrode of the lithium ion battery, then conveying into a third slurry system, and adding partial solvent in proportion to perform high-speed dispersion, so as to obtain primary slurry of the positive electrode of the lithium ion battery. The preparation method comprises the following steps: stirring and dispersing at a high speed, measuring by an online viscometer, conveying to 4 / 5 / 6 / 7 of slurry, carrying out pipeline ultrasonic defoaming in the conveying process, reducing slurry bubbles, conveying to a transfer stirring tank, stabilizing, and coating, so that the slurry preparation time can be effectively shortened, the cost is reduced, and the efficiency is improved; and the distribution uniformity of the composite slurry material, the electrode impedance, the specific capacity per gram of the composite material, the rate, the cycle performance and the like are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery slurry preparation and processing, and in particular to a slurrying process of lithium ion battery composite positive electrode slurry and its application. Background Art

[0002] Lithium battery positive electrode binders are mostly PVDF5130, HSV900, etc. Before preparing the slurry, it is necessary to dissolve the positive electrode binder PVDF5130 or HSV900 with the solvent NMP to form a glue solution, and then prepare the positive electrode slurry. The preparation process is mostly to mix the binder and the solvent to form a glue solution, and then add it to the mixing tank in different orders and different masses to complete the slurry preparation.

[0003] For example, Chinese patent CN112635715A discloses a positive electrode slurry for lithium-ion batteries, a homogenization method and use thereof, wherein the homogenization method comprises: during the stirring process, adding conductive agent powder and binder powder in sequence, adding part of the solvent in the form of spraying, then adding the positive electrode material powder, and adding the remaining solvent in the form of spraying, so as to prepare the positive electrode slurry for lithium-ion batteries. The present invention adds the conductive agent, binder and positive electrode material in the form of powder, sprays the solvent while adding the powder, continuously sprays the added solvent and the powder while stirring, and continuously kneads the powder so that the powder is stirred and dispersed uniformly. Within the preferred range of the present invention, the viscosity of the positive electrode slurry for lithium-ion batteries is 15000-22000mpa·s, and when the average fineness is 4-8μm, the total time from feeding to discharging is about 3.5h, which shortens the stirring time and saves costs.

[0004] For example, Chinese patent CN116532017A discloses a homogenization method for battery positive electrode materials, comprising the following steps: Step 1: Prepare raw materials: Mix the required battery positive electrode materials and other additives in a certain proportion to form a mixture. Step 2: Add solvent: Add the mixture to an appropriate amount of solvent and stir it thoroughly so that the mixture is evenly dispersed in the solvent. In the present invention, when high-power ultrasound is coupled to the mixed slurry, the slurry is compressed and expanded in high-pressure and low-pressure cycles, respectively. In the low-pressure cycle, tiny vacuum bubbles are generated, and these bubbles grow in multiple pressure cycles. In those cycles of bubble growth, the gas in the liquid is adsorbed to the bubble surface and released from the liquid when it has a large enough size, which greatly reduces the bubbles in the slurry and improves the homogenization effect.

[0005] For example, Chinese patent CN107910546A discloses a method for preparing a uniform slurry for a positive electrode of a lithium-ion battery, comprising: 1) weighing raw materials by weight: 85-95 parts of positive electrode ternary materials, 2-10 parts of binder polyvinylidene fluoride, 0.5-5 parts of conductive carbon black powder and 0.1-5 parts of surfactant; 2) measuring organic solvent; 3) dissolving the weighed binder polyvinylidene fluoride powder in the measured organic solvent, stirring for 1-5 hours to obtain a PVDF solution; 4) adding the weighed conductive carbon black powder to the PVDF solution prepared in step 4, stirring for 1-10 hours to prepare a conductive glue; 5) adding NCM dry powder to the conductive glue prepared in step 4), and adding the remaining organic solvent, adding a surfactant, stirring, and obtaining a uniform slurry for a positive electrode of a lithium-ion battery. The invention adjusts and improves the preparation process, and the obtained slurry can greatly improve the performance of lithium batteries. However, it has the problem of long homogenization time.

[0006] For example, Chinese patent CN 117174838 A discloses a positive electrode sheet and its preparation method and application. A preparation method of a positive electrode sheet comprises the following steps: S1, mixing a first positive electrode active material, a first conductive agent, a first binder and a first lithium supplement additive to obtain a first positive electrode slurry; mixing a second positive electrode active material, a second conductive agent, a second binder and a second lithium supplement additive to obtain a second positive electrode slurry; S2, coating the second positive electrode slurry on the surface of the positive electrode current collector, coating the first positive electrode slurry on the second positive electrode slurry, drying and cold pressing to obtain the positive electrode sheet; wherein the first positive electrode slurry is

[0007] The particle size D50 of the first lithium supplement additive is 0.3-1.5 μm, and the particle size D50 of the second lithium supplement additive is 2-5 μm. The positive electrode sheet of the present application has the advantage of improving the cycle performance of thick electrode lithium batteries.

[0008] For example, Chinese patent CN115832172A discloses a positive electrode slurry and a preparation method thereof, and a positive electrode sheet. The preparation method of the positive electrode slurry includes the following steps: first, the positive electrode active material and the conductive agent are dry-mixed to obtain a dry powder mixture, and the binder and the solvent are evenly mixed to obtain a binder glue. Secondly, the first part of the binder glue is added to the dry powder mixture, and stirred and kneaded to obtain a first mixture. Subsequently, the second part of the binder glue is added to the first mixture, and stirred and dispersed to obtain a second mixture. Finally, the solvent is added to the second mixture, and stirred and dispersed to obtain a positive electrode slurry. The preparation method of the positive electrode slurry of the present application makes the slurry more evenly dispersed and more consistent, which not only greatly improves the problem of powder shedding of the coated electrode sheet and improves the peeling force of the electrode sheet, but also effectively shortens the process of the positive electrode slurry process, greatly reducing the time cost of preparing the positive electrode slurry.

[0009] For example, Chinese patent CN114156431B discloses a positive electrode homogenization method, positive electrode slurry and its application. The positive electrode homogenization method comprises the following steps: 1) mixing a conductive agent auxiliary material, a first binder and a positive electrode active material into a mass; 2) mixing a PVP dispersion liquid and the mass to obtain a first dispersion; 3) using the first dispersion, a conductive agent main material and a second binder to perform slurry homogenization to obtain a positive electrode slurry; the first binder comprises at least one of polyimide and modified polyimide. The method of the present invention can improve the performance of the positive electrode active material while simplifying the coating process. Summary of the invention

[0010] The object of the present invention is to provide a slurry and an electrode with higher uniformity and a battery cell thereof.

[0011] The present invention also aims to provide a homogenization process method which can shorten pulping time, improve efficiency and reduce energy consumption.

[0012] The present invention also aims to provide a process method that can be used for automated integration and operation.

[0013] The purpose of the present invention is to provide a slurrying process method for a composite positive electrode slurry, improve the distribution uniformity of related raw materials in the slurry, reduce electrode impedance, improve low temperature and cycle performance, and improve slurry fluidity and electrode performance, etc., so that it can be applied to secondary battery positive electrode sheets and secondary batteries and have good performance.

[0014] In order to achieve the above object, the present invention adopts the following technical solutions:

[0015] A slurrying process for lithium-ion battery composite positive electrode slurry, such as a process Figure 1 As shown, it includes the first slurry and the second slurry obtained by step-by-step pulping, and the third slurry, the fourth slurry, the fifth slurry, the sixth slurry and the seventh slurry obtained by mixing and adjusting the pulping;

[0016] The first slurry comprises a positive electrode material 1, a binder 1, a conductive agent 1, a lithium supplement agent 1, a conductive slurry 1 and a solvent; the second slurry comprises a positive electrode material 2, a binder 2, a conductive agent 2, a lithium supplement agent 2, a conductive slurry 2 and a solvent; the third slurry comprises the first slurry, the second slurry and a solvent; the fourth / fifth / sixth / seventh slurry comprises the third slurry and a solvent;

[0017] The positive electrode material 1 and the positive electrode material 2 are positive electrode raw materials of different structural types and particle sizes; the binder 1 and the binder 2 can be the same or different; the conductive agent 1 and the conductive agent 2 can be the same or different; the lithium supplement agent 1 and the lithium supplement agent 2 can be the same or different; the conductive paste 1 and the conductive paste 2 can be the same or different;

[0018] The first slurry and the second slurry may further include a dispersant.

[0019] The present invention provides a slurrying process for a lithium-ion battery composite positive electrode slurry, such as the process Figure 1 As shown, the following steps are included:

[0020] S1: Under high-speed mixing and stirring conditions, the positive electrode material, the conductive agent, the binder, and the lithium supplement agent are continuously added to the first slurry and the second slurry preparation system in proportion, and the mixture is transported to the stirring tank after high-speed mixing in a high-speed mixer, and part of the solvent is continuously added in proportion in the form of spraying for stirring and kneading for a certain time;

[0021] S2: Under stirring and dispersing conditions, part of the solvent and all of the conductive slurry and dispersant are continuously added in a spraying form according to the proportion. After the materials are added, they are stirred at high speed for a certain period of time under vacuum conditions to complete the primary preparation of the first slurry and the second slurry respectively;

[0022] S3: under stirring and dispersing conditions, the first slurry and the second slurry are transported to the high-speed stirring and dispersing machine system of the third slurry according to the designed ratio, and part of the solvent is added to perform high-speed dispersion for a certain period of time to obtain the third slurry, and then the viscosity is monitored and regulated by an online viscosity tester, and then the bubbles are automatically transported to the fourth slurry system in the next step by ultrasonic elimination of the pipeline;

[0023] S4: under stirring and dispersing conditions, the third slurry is transported to the high-speed stirring and dispersing machine system of the fourth slurry through a pipeline, and part of the solvent is added for high-speed dispersion to obtain the fourth slurry, and then the viscosity is monitored and controlled by an online viscosity tester, and then the bubbles are eliminated by ultrasonic pipeline and automatically transported to the next step (fifth) slurry system; that is, the fourth / 5th / 6th / 7th slurries are respectively prepared by repeating the third slurry to the fourth slurry steps, and the amount of solvent added to the fourth slurry to the seventh slurry can be automatically calculated and added by proportionally controlling the flow rate according to the data of online slurry viscosity feedback;

[0024] S5: under stirring conditions, conveying the seventh slurry to the transfer stirring tank, and after the addition is completed, continuing to stir for a certain period of time under a certain vacuum degree to prepare the lithium-ion battery positive electrode composite slurry.

[0025] The first slurry and the second slurry are slurries prepared by combining different types of raw materials and formulation systems, and the positive electrode material, conductive agent, lithium supplement agent and binder are all in powder form.

[0026] The present invention also provides a slurrying process for composite positive electrode slurry of lithium ion batteries, wherein the positive electrode material provided is a composite slurry prepared by combining raw materials of different structural types, particle sizes and formulation systems.

[0027] The following is a detailed description:

[0028] Step (1):

[0029] The positive electrode material 1 is selected from one or more of the layered micron-sized materials, and the single crystal particle size D 50 The particle size D of the polycrystalline particles can be 2 to 6 μm, preferably 2.2 to 4.8 μm. 50 It can be 7 to 16 μm, preferably 9 to 12 μm.

[0030] The positive electrode material 2 is selected to be composed of one or more polyanionic nano-scale or submicron-scale materials, and its nano-scale particles can be 200-1000nm, preferably 500-800nm, and its submicron-scale particles can be 0.1μm-1.5μm.

[0031] In some embodiments, the positive electrode material 1 may be a combination of one or more of NCM, NCA, NCMA, LCO, LMO, NNFC, NNFM, NNFCM, etc.;

[0032] In some embodiments, the positive electrode material 2 may be a combination of one or more of LFP, LMFP, LVPF, NVPF, NFP, etc.;

[0033] In some embodiments, binder 1 or binder 2 can be one or a combination of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA) or acrylonitrile copolymer; the specific model can be one or a mixture of two or more of Solvay 5130, FL2100, HSV900, HSV600, etc.

[0034] Preferably, the binder 1 in the first slurry system is Solvay 5130, FL2100, or HSV900; and the binder 2 in the second slurry system is preferably HSV900, a composite of HSV900+Solvay 5130, or a composite of HSV900+FL2100.

[0035] In some embodiments, the solvent is a non-aqueous solvent, which may be any one of N-methylpyrrolidone, dimethylacetamide, or dimethyl sulfoxide, or a combination of at least two thereof.

[0036] Preferably, the solvent is N-methylpyrrolidone (NMP).

[0037] In some embodiments, the conductive agent 1 and the conductive agent 2 can be one or a combination of at least two of powder materials such as carbon black, graphite powder, carbon fiber, metal oxide conductive agent, and fast ion conductive agent.

[0038] Preferably, it is carbon black, metal oxide, fast ion conductive agent or a combination of at least two thereof.

[0039] In some embodiments, the carbon black may be one of the conductive carbon blacks SP, Super P-Li, KB, AB, etc., or a combination of at least two thereof.

[0040] Preferably, the conductive carbon black is one of SP, Super P-Li, KB, etc., or a combination of at least two thereof.

[0041] In some embodiments, the graphite powder may be one or two or more composite materials such as KS-6, KS-15, and SFG-6.

[0042] The preferred conductive graphite powder is KS-6 or SFG-6, or a combination of two or more thereof.

[0043] In some embodiments, the carbon fiber conductive agent may be one or a combination of at least two of nanocarbon fibers (VGCF), carbon nanotubes (SWNTs, MWNTs) and carbon fibers (GN).

[0044] Preferably, the carbon fiber conductive agent is selected from one or a combination of at least two of nanocarbon fibers (VGCF) and carbon nanotubes (SWNTs, MWNTs).

[0045] In some embodiments, the metal oxide conductive agent may be ZnO, SnO 2 , Sb 2 O 3 、In 2 O 3 、TiO 2 , ATO powder, etc. or one or two or more composite materials.

[0046] Preferably, it is Sb 2 O 3 、In 2 O 3 、TiO 2 , ATO powder or a combination of two or more.

[0047] In some embodiments, the fast ion conductor can be a combination of one or more solid electrolyte fast ion conductor materials such as LATP, LAZP, LLZP, LLZO, LLZTO, etc.; or Li 3 YC 6 , Li 3 Y(Br 3 Cl 3 )、Li 3 oeLh 6 , Li 3 InCI 6 , Li 3 oeLh6 , Li 3 I 6 , Li 3 InBr 6 , Li 3 InI 6 or a combination of one or more halide fast ion conductor materials such as Beta alumina, Nasicon (Na 3 Zr 2 Si 2 PO 12 )A combination of one or more sodium ion fast ion conductor materials.

[0048] Preferably, it is selected from one or two or more composite fast ion conductive materials of solid electrolytes and halides.

[0049] In some embodiments, the conductive agent 1 in the first slurry system is preferably a combination of one or more of SP, Super P-Li, and KS-6; the conductive agent 2 in the second slurry system is preferably a combination of one or more of KS-6, SFG-6, and KB.

[0050] In some embodiments, the lithium supplement agent 1 and the lithium supplement agent 2 can be lithium-rich nickel acid, lithium-rich cobalt acid, lithium-rich iron acid, Li 2 S / Co, LiF / Co, Li 2 O / Co、Li 2 O. Li 2 O 2 , Li 3 N.Li 2 S and other powder materials or a composite material of two or more.

[0051] Preferably, it is a material composed of one or two or more of lithium-rich nickel acid, lithium-rich cobalt acid, and lithium-rich iron acid in proportion.

[0052] In some embodiments, conductive paste 1 and conductive paste 2 are conductive pastes prepared by compounding carbon nanotubes / graphene with a conductive agent; preferably, the conductive agent is one of the powder materials of carbon black, graphite powder, carbon fiber, metal oxide conductive agent, and fast ion conductive agent.

[0053] The conductive slurry 1 / 2 is carbon nanotubes or graphene (2.0-6.0 parts), conductive agent (0.1-3.0 parts), NMP solvent (85-95 parts), dispersant (such as PVP) (0.1-1.5 parts), binder (such as PVDF) (0.001-0.05 parts) which are put into proportion and prepared by ball milling / stirring-transfer tank-grinding 1 (coarse)-transfer tank-grinding 2 (fine)-transfer tank-grinding 3 (fine)-transfer tank-emulsification-transfer tank-finished product.

[0054] In some embodiments, the conductive liquid 1 in the first slurry system of the positive electrode material 1 is preferably carbon nanotubes or a conductive slurry prepared therefrom, and the conductive liquid 2 in the second slurry system of the positive electrode material 2 is preferably graphene or a conductive slurry prepared therefrom.

[0055] In some embodiments, the weight ratio of positive electrode material 1: binder 1: conductive agent 1: lithium supplement agent 1: conductive slurry 1: dispersant 1 in the first slurry system is (88.0-99.0): (0.8-2.0): (0.1-5.0): (0.1-4.0): (0.02-1.8): (0.01-0.5), and the solid content of the slurry is 65-80%.

[0056] In some embodiments, the weight ratio of positive electrode material 2: binder 2: conductive agent 2: lithium supplement agent 2: conductive slurry 2: dispersant 2 in the second slurry system is (85.0~98.5): (1.2~4.0): (0.2~8.0): (0.1-5.0) (0.01~2.0): (0.01~0.5), and the solid content of the slurry is 52~68%.

[0057] In some embodiments, the speed of the pipeline high-speed mixer can be 2000-5000 rpm, and the mixing time can be 1-10S; preferably, the speed is 2500-4500 rpm, and the mixing time is 2-8S; more preferably, the speed is 2800-4200 rpm, and the mixing time is 3-6S;

[0058] In some embodiments, the stirring speed may preferably be 10 to 30 rpm, and the dispersion speed may preferably be 1200 to 2500 rpm;

[0059] In some embodiments, the kneading time may preferably be 30 to 60 minutes, and more preferably may be 45 to 60 minutes;

[0060] In some embodiments, the solvent addition ratio may be 55-65% of the total solvent weight.

[0061] Step (2):

[0062] In some embodiments, the dispersant is one or two or more of an amphoteric dispersant, a polymer copolymer dispersant, a PVP dispersant, a polyether dispersant, a polyester dispersant, a carboxylic acid dispersant, a sulfonic acid dispersant, a combined dispersant, etc.; for example, the dispersant specification model is selected as a combination of one or more of D-650, PVP-K30, VOK-Disper 41000, Anjeka6830, DIS-730A, CGPS ​​313D, CGPS ​​313D8, CGPS ​​513, CGPS277B, LD-1128, YTF003, PEG, and ethanol;

[0063] Preferably, the material is selected from one or a composite of two or more (in proportion) of D-650, PVP-K30, VOK-Disper 41000, Anjeka6830, CGPS ​​313D8, CGPS513, and YTF003.

[0064] In some embodiments, the stirring speed may preferably be 15 to 35 rpm, and the dispersion speed may preferably be 1500 to 3200 rpm;

[0065] In some embodiments, the stirring time may preferably be 60 to 120 minutes, and more preferably may be 60 to 90 minutes;

[0066] In some embodiments, the vacuum degree is ≤-98 kPa, and the internal temperature of the stirring tank is ≤50°C;

[0067] In some embodiments, the solvent addition ratio may be 20 to 35% of the total solvent weight;

[0068] In some embodiments, the first slurry viscosity control range may be 12000-15000 mpa·s, and the second slurry viscosity range may be 13000-16000 mpa·s;

[0069] Step (3):

[0070] In some embodiments, the composite ratio of positive electrode material 1:positive electrode material 2 in the first slurry and the second slurry system is (5-92):(8-95);

[0071] Preferably, the first slurry: the second slurry = (10-88): (12-90), more preferably, the first slurry: the second slurry = (15-80): (20-85);

[0072] In some embodiments, the slurry high-speed dispersion speed may be 3000-8000 rpm; the slurry high-speed dispersion time may be 10-90 s;

[0073] In some embodiments, the solvent addition ratio may be 6 to 10% of the total solvent weight;

[0074] In some embodiments, the third slurry viscosity control range may be 6000 to 10000 mPa·s;

[0075] In some embodiments, the ultrasonic frequency for defoaming pipeline slurry may be preferably 10-35 Hz, and the time may be 10-90 s, more preferably 15-25 Hz, and 30-60 s;

[0076] Step (4):

[0077] In some embodiments, the slurry high-speed dispersion speed may be 3000 to 8000 rpm; the slurry high-speed dispersion time may be 10 to 60 s;

[0078] In some embodiments, the fourth slurry viscosity control range may be 5000-9000 mPa·s, the fifth slurry viscosity control range may be 4000-8000 mPa·s, the sixth slurry viscosity control range may be 4000-7500 mPa·s; the seventh slurry viscosity control range may be 3500-7500 mPa·s;

[0079] In some embodiments, the fourth slurry solvent addition ratio may be 1-2% of the total solvent weight;

[0080] In some embodiments, the solvent addition ratio of the 5th / 6th / 7th slurry viscosity conditions can be 1-2% of the solvent weight respectively;

[0081] In some embodiments, the ultrasonic frequency for defoaming pipeline slurry may be preferably 10-35 Hz, and the time may be 10-90 s, more preferably 15-25 Hz, and 30-60 s;

[0082] Step (5):

[0083] In some embodiments, the low-speed stirring speed may be 2 to 10 rpm; the low-speed dispersion speed may be 100 to 600 rpm;

[0084] In some embodiments, the stirring and dispersing time may be 30 to 60 minutes, preferably 30 to 45 minutes;

[0085] In some embodiments, the vacuum degree is ≤-98 kPa, and the internal temperature of the stirring tank is ≤50°C;

[0086] In some embodiments, the slurry viscosity is controlled in the range of 3000-7500 mPa·s;

[0087] In a third aspect, the present invention provides a use of the above-mentioned composite positive electrode slurry in preparing a positive electrode sheet for a secondary battery or a secondary battery.

[0088] Preferably, the secondary battery includes a soft-pack, square, or cylindrical lithium-ion battery.

[0089] The secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, a shell, a metal tab, a connecting sheet, etc.;

[0090] The positive electrode sheet includes 1 / 2 positive electrode material, 1 / 2 conductive agent, 1 / 2 binder, 1 / 2 lithium supplement agent, 1 / 2 dispersant, 1 / 2 conductive slurry, foil (aluminum foil or carbon-coated aluminum foil), positive electrode ear and positive electrode connecting sheet, etc.;

[0091] The negative electrode sheet includes one or more composite materials of natural graphite / artificial graphite / silicon carbon / silicon oxygen, a conductive agent, a binder (CMC, PAA, etc.), a thickener (SBR, etc.), a conductive slurry, a foil (copper foil or carbon-coated copper foil), a negative electrode ear and a negative electrode connecting sheet, etc.;

[0092] The diaphragm includes PP, PE, PP / PE / PP composite film, composite ceramic diaphragm, solid electrolyte diaphragm, etc.;

[0093] The electrolyte includes HDGT's own formula or raw materials that meet performance requirements;

[0094] The shell includes aluminum-plastic composite film, square aluminum shell / steel shell, round aluminum shell / steel shell, square plastic shell, etc.

[0095] The positive electrode ear or positive electrode connecting piece is an aluminum strip, a composite aluminum strip, etc.;

[0096] The negative electrode ear and the negative electrode connecting piece are nickel strip, composite nickel strip, copper-nickel composite strip, etc.;

[0097] The foil material includes aluminum foil or carbon-coated aluminum foil, copper foil or carbon-coated copper foil, etc.;

[0098] The invention also discloses a slurry obtained by the composite positive electrode slurry or the method, or a secondary battery positive electrode sheet or a secondary battery prepared by the method.

[0099] Technical effects:

[0100] The invention adopts a process of dry-wet step pulping and then composite homogenization based on the traditional wet homogenization process or semi-dry homogenization process.

[0101] The slurrying process of the composite positive electrode slurry of the present invention further adopts a synchronous classification slurrying method, and uses a pipeline high-speed mixer to mix the relevant dry powder raw materials at high speed and then knead and stir them, and each dry powder is evenly added in proportion, which is conducive to more uniform kneading and homogenization according to different types, and can effectively improve the uniform distribution of relevant raw materials, which is conducive to improving the coverage and bonding performance of the glue on the surface of different types of raw materials, improving the distribution uniformity of relevant raw materials in the slurry and electrode, reducing the electrode impedance, and improving low temperature and cycle performance.

[0102] The slurrying process of the composite positive electrode slurry described in the present invention further uses different types of slurries for compounding, which can effectively improve the thermal stability and safety of layered structure materials, and can effectively improve the low temperature performance and rate performance of polyanionic materials.

[0103] The slurry homogenization process of the composite positive electrode slurry of the present invention further adopts multi-stage slurry dispersion, which can effectively improve the distribution uniformity of the components of the composite slurry, reduce the slurry viscosity adjustment time, and further improve the slurry stability and electrode processing performance;

[0104] The homogenization process method of the composite positive electrode slurry of the present invention further adopts pipeline ultrasonic defoaming, which can effectively reduce the bubbles generated during the high-speed dispersion viscosity adjustment process and effectively reduce the defoaming and overall homogenization time.

[0105] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS

[0106] Figure 1 It is a schematic diagram of the homogenization process of the composite positive electrode slurry in the patent of the present invention;

[0107] Figure 2 SEM images of Examples 1-4 and Comparative Examples 1-3 of the present invention;

[0108] Figure 3 The charge and discharge curve diagram of the slurry half-cell of Examples 1-4 of the present invention;

[0109] Figure 4 The half-cell rate discharge curve of slurry in Examples 1-4 of the present invention;

[0110] Figure 5 Static slurry viscosity variation trend diagram of Examples 1-4 and Comparative Examples 1-3 of the present invention;

[0111] Figure 6Full battery cycle performance trend diagram of Example 1-2 and Comparative Example 1-2 of the present invention;

[0112] Figure 7 This is a schematic diagram of the structure of the pipeline high-speed mixer in the patent of the present invention;

[0113] Figure 8 This is a schematic diagram of the slurry dispersing machine device in the patent of the present invention;

[0114] Fig. 9 This is a schematic diagram of the pipeline ultrasonic defoaming device in the patent of this invention. DETAILED DESCRIPTION

[0115] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.

[0116] Unless otherwise specified, the positive electrode materials used in the examples (NCM650728: D50 = 3.7 ±

[0117] 0.6um, LMFP: D50 = 0.9 ± 0.5um), conductive agent (Super P-Li, LiTX 300), binder (Solvay 5130, HSV900, FL2100), lithium supplement (lithium-rich nickel acid, lithium-rich ferric acid), conductive slurry (MWCNTs), dispersant (D-650, CGPS ​​313D8, Anjeka6830, PVP-K30, YTF003), solvent (NMP), etc. are all conventional raw materials in the art.

[0118] The conductive slurry 1 / 2 is prepared by a process of ball milling / stirring-transfer tank-grinding 1 (coarse)-transfer tank-grinding 2 (fine)-transfer tank-grinding 3 (fine)-transfer tank-emulsification-transfer tank-finished product, etc., and the corresponding dosage ratios of the following embodiments and comparative examples are obtained.

[0119] Example 1

[0120] like Figure 1 As shown in the flow chart, this embodiment provides a homogenization process for a composite positive electrode slurry, and the specific steps are as follows (Examples 2 and 3 adopt the same steps as follows):

[0121] S1: Under high-speed mixing and stirring conditions, the positive electrode material, the conductive agent, the lithium supplement agent and the binder are continuously added in proportion to the first slurry and the second slurry preparation system respectively, and the mixture is transported to the stirring tank after high-speed mixing in the high-speed mixer, and part of the solvent is continuously added in proportion in the form of spraying for stirring and kneading for a certain time;

[0122] S2: Under stirring and dispersing conditions, part of the solvent and all of the conductive slurry and dispersant are continuously added in a spraying form according to the proportion. After the materials are added, they are stirred at high speed for a certain period of time under vacuum conditions to complete the primary preparation of the first slurry and the second slurry respectively;

[0123] S3: under stirring and dispersing conditions, the first slurry and the second slurry are transported to the high-speed stirring and dispersing machine system of the third slurry according to the designed ratio, and part of the solvent is added to perform high-speed dispersion for a certain period of time to obtain the third slurry, and then the viscosity is monitored and controlled by an online viscosity tester, and then the bubbles are automatically transported to the fourth slurry system in the next step by ultrasonic elimination of the pipeline;

[0124] S4: under stirring and dispersing conditions, the third slurry is transported to the high-speed stirring and dispersing machine system of the fourth slurry through a pipeline, and part of the solvent is added for high-speed dispersion to obtain the fourth slurry, and then the viscosity is monitored and controlled by an online viscosity tester, and then the bubbles are automatically eliminated by ultrasonic pipeline and transported to the fourth slurry system in the next step; that is, the fourth / 5th / 6th / 7th slurries are respectively prepared by repeating the steps of the third slurry to the fourth slurry, and the amount of solvent added to the fourth slurry to the seventh slurry can be automatically calculated and added by proportionally controlling the flow rate according to the data of the online slurry viscosity feedback;

[0125] S5: under stirring conditions, conveying the seventh slurry to the transfer stirring tank, and after the addition is completed, continuing to stir for a certain period of time under a certain vacuum degree to prepare the lithium-ion battery positive electrode composite slurry.

[0126] The specific step parameters are:

[0127] S1: In the first slurry system, NCM650728 (34.0 kg), Solvay 5130 (0.385 kg), lithium-rich nickel acid (0.35 kg), and LiTX300 (0.315 kg) were added at the mass ratio of positive electrode material 1: binder 1: conductive agent 1: lithium supplement agent 1: conductive slurry 1: dispersant 1 = 97.1: 1.1: 0.9: 1: 0.8: 0.1, and after high-speed mixing at 3200 rpm / 4s, they were transported to a stirring tank, and NMP (3.99 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1600 rpm, and kneaded and stirred for 45 minutes;

[0128] In the second slurry system, according to the mass ratio of positive electrode material 2: binder 2: conductive agent 2: lithium supplement agent 2: conductive slurry 2: dispersant 2 = 96.4: 1.5: 1.1: 1: 0.85: 0.15, LMFP (6.0 kg), Solvay 5130 (0.093 kg), lithium-rich nickel acid (0.062 kg), and LiTX300 (0.068 kg) were added simultaneously, and after high-speed mixing at 3800 rpm / 4 s, they were transported to a stirring tank, and NMP (1.781 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1800 rpm, and kneading and stirring were performed for 45 minutes;

[0129] S2: Under stirring conditions, MWCNTs conductive slurry -5% (5.602 kg), dispersant D-650 (0.035 kg), and NMP (1.995 kg) were gradually and evenly added to the first slurry system by spraying, and then stirred for 90 minutes at a stirring speed of 25 rpm, a dispersion speed of 3200 rpm, and a vacuum degree of ≤-98 kPa;

[0130] Under stirring conditions, MWCNTs conductive slurry -5% (1.058 kg), dispersant CGPS ​​313D8 (0.009 kg), and NMP (0.890 kg) were gradually and evenly added to the kneaded second slurry system by spraying, and then stirred for 90 minutes at a stirring speed of 25 rpm, a dispersion speed of 3500 rpm, and a vacuum degree of ≤-98 kPa;

[0131] S3: input 46.322 kg of the first slurry, 9.899 kg of the second slurry, and NMP (0.770 kg) into the slurry 3 system under dispersion conditions, disperse at 4500 rpm for 60 s, and control the viscosity at 6000-9000 mPa·s;

[0132] S4: input the third slurry 56.991 kg and NMP (0.192 kg) into the slurry 4 system under dispersion conditions, disperse at 4200 rpm for 45 seconds, and control the viscosity at 5000-8000 mPa·s; the ultrasonic condition is 20 Hz / 45 seconds;

[0133] Under the dispersion condition, the fourth slurry 57.183 kg and NMP (0.192 kg) were input into the slurry 5 system, and the viscosity was adjusted by dispersing at 4200 rpm for 45 seconds, and the viscosity was controlled at 5000-7000 mPa·s;

[0134] Under the dispersion condition, 57.375 kg of the fifth slurry and NMP (0.192 kg) were input into the slurry 6 system, and the viscosity was adjusted by dispersing at 4000 rpm for 45 seconds, and the viscosity was controlled at 4000-7000 mPa·s;

[0135] Under the dispersion condition, 57.567 kg of the sixth slurry and NMP (0.096 kg) were input into the slurry system 7, and the viscosity was adjusted by dispersing at 3600 rpm for 45 seconds, and the viscosity was controlled at 3500-6500 mPa·s;

[0136] S5: The seventh slurry (57.663 kg) was input into the transfer stirring tank under stirring and dispersing conditions, and stirred for 30 min at a stirring speed of 5 rpm, a dispersing speed of 400 rpm, and a vacuum degree of ≤-98 kPa; the final slurry viscosity was controlled at 3500-6500 mpa·s, and the solid content was controlled at 72.0±1.5%.

[0137] Example 2

[0138] like Figure 1 As shown in the flow chart, this embodiment provides a slurrying process for composite positive electrode slurry (the method is the same as that in Example 1), and the specific step parameters are as follows:

[0139] S1: In the first slurry system, NCM650728 (12.0 kg), Solvay 5130 (0.136 kg), lithium-rich nickel acid (0.124 kg), and LiTX300 (0.111 kg) were added at a mass ratio of positive electrode material 1: binder 1: conductive agent 1: lithium supplement agent 1: conductive slurry 1: dispersant 1 = 97.1: 1.1: 0.9: 1: 0.8: 0.1, and after high-speed mixing at 3200 rpm / 4s, they were transported to a stirring tank, and NMP (1.408 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1600 rpm, and the mixture was kneaded and stirred for 45 minutes;

[0140] In the second slurry system, according to the mass ratio of positive electrode material 2: binder 2: conductive agent 2: lithium supplement agent 2: conductive slurry 2: dispersant 2 = 96.1: 1.5: 1.35: 1: 0.90: 0.15, LMFP (28.0 kg), Solvay 5130 (0.437 kg), lithium-rich nickel acid (0.291 kg), and LiTX300 (0.393 kg) were added simultaneously, and after high-speed mixing at 3800 rpm and 4 s, they were transported to a stirring tank, and NMP (8.171 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1800 rpm, and kneaded and stirred for 45 minutes;

[0141] S2: Under stirring conditions, MWCNTs conductive slurry -5wt% (1.977kg), dispersant D-650 (0.012kg), and NMP (0.704kg) were gradually and evenly added to the first slurry system by spraying, and then stirred for 90min at a stirring speed of 25rpm, a dispersion speed of 3200rpm, and a vacuum degree of ≤-98kPa;

[0142] Under stirring conditions, MWCNTs conductive slurry -5wt% (5.245kg), dispersant CGPS ​​313D8 (0.044kg), and NMP (4.085kg) were gradually and evenly added to the kneaded second slurry system by spraying, and then stirred for 90 minutes at a stirring speed of 25rpm, a dispersion speed of 3500rpm, and a vacuum degree of ≤-98kPa;

[0143] S3: input 16.35 kg of the first slurry, 46.375 kg of the second slurry, and NMP (1.277 kg) into the slurry 3 system under dispersion conditions, disperse at 4500 rpm for 60 s, and control the viscosity at 6000-9000 mPa·s;

[0144] S4: input the third slurry 64.002 kg and NMP (0.319 kg) into the slurry 4 system under dispersion conditions, disperse at 4200 rpm for 45 seconds, and control the viscosity at 5000-8000 mPa·s; the ultrasonic condition is 20 Hz / 45 seconds;

[0145] Under the dispersion condition, 64.321 kg of the fourth slurry and NMP (0.319 kg) were input into the slurry 5 system, and the viscosity was adjusted by dispersing at 4200 rpm for 45 seconds, and the viscosity was controlled at 5000-7000 mPa·s;

[0146] Under the dispersion condition, 64.64 kg of the fifth slurry and NMP (0.319 kg) were input into the slurry 6 system, and the viscosity was adjusted by dispersing at 4000 rpm for 45 seconds, and the viscosity was controlled at 4000-7000 mPa·s;

[0147] Under the dispersion condition, 64.959 kg of the sixth slurry and NMP (0.160 kg) were input into the slurry system 7, and the viscosity was adjusted by dispersing at 3600 rpm for 45 seconds, and the viscosity was controlled at 3500-6500 mpa·s;

[0148] S5: The seventh slurry (65.119 kg) was input into the transfer stirring tank under stirring and dispersing conditions, and stirred for 30 min at a stirring speed of 5 rpm, a dispersing speed of 400 rpm, and a vacuum degree of ≤-98 kPa; the final slurry viscosity was controlled at 3500-6500 mpa·s, and the solid content was controlled at 64.5±1.5%.

[0149] Example 3

[0150] like Figure 1 As shown in the flow chart, this embodiment provides a slurrying process for composite positive electrode slurry (the method is the same as that in Example 1), and the specific steps are as follows:

[0151] S1: In the first slurry system, NCM650728 (20.0 kg), FL2100 (0.227 kg), lithium-rich ferric acid (0.206 kg), and Super P-Li (0.185 kg) were added at the mass ratio of positive electrode material 1: binder 1: conductive agent 1: lithium supplement agent 1: conductive slurry 1: dispersant 1 = 97.1: 1.1: 0.9: 1: 0.8: 0.1, and after high-speed mixing at 3200 rpm / 4s, they were transported to a stirring tank, and NMP (2.347 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1600 rpm, and the mixture was kneaded and stirred for 45 minutes;

[0152] In the second slurry system, according to the mass ratio of positive electrode material 2: binder 2: conductive agent 2: lithium supplement agent 2: conductive slurry 2: dispersant 2 = 96.1: 1.65: 1.20: 1: 0.90: 0.15, LMFP (20.0 kg), FL2100 (0.2744 kg), HSV900 (0.0686 kg), lithium-rich ferric acid (0.208 kg), and Super P-Li (0.250 kg) were added simultaneously, and after high-speed mixing at 3800 rpm and 4 s, they were transported to a stirring tank, and NMP (5.836 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1800 rpm, and kneaded and stirred for 45 minutes;

[0153] S2: Under stirring conditions, MWCNTs conductive slurry -5% (3.296 kg), dispersant D-650 (0.021 kg), and NMP (1.174 kg) were gradually and evenly added to the first slurry system by spraying, and then stirred for 90 minutes at a stirring speed of 25 rpm, a dispersion speed of 3200 rpm, and a vacuum degree of ≤-98 kPa;

[0154] Under stirring conditions, MWCNTs conductive slurry -5% (3.746 kg), dispersant CGPS ​​313D8 (0.032 kg), and NMP (2.918 kg) were gradually and evenly added to the kneaded second slurry system by spraying, and then stirred for 90 minutes at a stirring speed of 25 rpm, a dispersion speed of 3500 rpm, and a vacuum degree of ≤-98 kPa;

[0155] S3: input 27.249 kg of the first slurry, 33.125 kg of the second slurry, and NMP (1.091 kg) into the slurry 3 system under dispersion conditions, disperse at 4500 rpm for 60 s, and control the viscosity at 6000-9000 mPa·s;

[0156] S4: input the third slurry 61.465 kg and NMP (0.273 kg) into the slurry 4 system under dispersion conditions, disperse at 4200 rpm for 45 seconds, and control the viscosity at 5000-8000 mPa·s; the ultrasonic condition is 20 Hz / 45 seconds;

[0157] Under the dispersion condition, 61.738 kg of the fourth slurry and NMP (0.273 kg) were input into the slurry 5 system, and the viscosity was adjusted by dispersing at 4200 rpm for 45 seconds, and the viscosity was controlled at 5000-7000 mPa·s;

[0158] Under the dispersion condition, 2.011 kg of the fifth slurry 6 and NMP (0.273 kg) were input into the slurry 6 system, and the viscosity was adjusted by dispersing at 4000 rpm for 45 seconds, and the viscosity was controlled at 4000-7000 mPa·s;

[0159] Under the dispersion condition, 62.284 kg of the sixth slurry and NMP (0.136 kg) were input into the slurry system 7, and the viscosity was adjusted by dispersing at 3600 rpm for 45 seconds, and the viscosity was controlled at 3500-6500 mPa·s;

[0160] S5: The seventh slurry (62.42 kg) was input into the transfer stirring tank under stirring and dispersing conditions, and stirred for 30 min at a stirring speed of 5 rpm, a dispersing speed of 400 rpm, and a vacuum degree of ≤-98 kPa; the final slurry viscosity was controlled at 3500-6500 mpa·s, and the solid content was controlled at 67.5±1.5%.

[0161] Example 4

[0162] like Figure 1 As shown in the flow chart, this embodiment provides a slurrying process for composite positive electrode slurry (the method is the same as that in Example 1), and the specific steps are as follows:

[0163] S1: In the first slurry system, NCM650728 (20.0 kg), FL2100 (0.228 kg), Super P-Li (0.186 kg), and lithium-rich nickel acid (0.104 kg) were added at a mass ratio of positive electrode material 1: binder 1: conductive agent 1: lithium supplement agent 1: conductive slurry 1: dispersant 1 = 96.6:1.1:0.9:1:0.8:0.1, and after high-speed mixing at 3200 rpm / 4s, they were transported to a stirring tank, and NMP (2.359 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1600 rpm, and the mixture was kneaded and stirred for 45 minutes;

[0164] In the second slurry system, according to the mass ratio of positive electrode material 2: binder 2: conductive agent 2: lithium supplement agent 2: conductive slurry 2: dispersant 2 = 95.6: 1.65: 1.20: 1: 0.90: 0.15, LMFP (20.0 kg), FL2100 (0.2744 kg), HSV900 (0.0686 kg), Super P-Li (0.250 kg), and lithium-rich ferric acid (0.105 kg) were added at the same time, and after high-speed mixing at 3800 rpm and 4 s, they were transported to a stirring tank, and NMP (5.867 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1800 rpm, and kneaded and stirred for 45 minutes;

[0165] S2: Under stirring conditions, MWCNTs conductive slurry -5wt% (3.313kg), dispersant D-650 (0.021kg), and NMP (1.180kg) were gradually and evenly added to the first slurry system by spraying, and then stirred for 90min at a stirring speed of 25rpm, a dispersion speed of 3200rpm, and a vacuum degree of ≤-98kPa;

[0166] Under stirring conditions, MWCNTs conductive slurry -5wt% (3.766kg), dispersant CGPS ​​313D8 (0.032kg), and NMP (2.933kg) were gradually and evenly added to the kneaded second slurry system by spraying, and then stirred for 90 minutes at a stirring speed of 25rpm, a dispersion speed of 3500rpm, and a vacuum degree of ≤-98kPa;

[0167] S3: input 27.369 kg of the first slurry, 33.267 kg of the second slurry, and NMP (1.097 kg) into the slurry 3 system under dispersion conditions, disperse at 4500 rpm for 60 s, and control the viscosity at 6000-9000 mPa·s;

[0168] S4: input the third slurry 61.733 kg and NMP (0.274 kg) into the slurry 4 system under dispersion conditions, disperse at 4200 rpm for 45 seconds, and control the viscosity at 5000-8000 mPa·s; the ultrasonic condition is 20 Hz / 45 seconds;

[0169] Under the dispersion condition, 62.007 kg of the fourth slurry and NMP (0.274 kg) were input into the slurry 5 system, and the viscosity was adjusted by dispersing at 4200 rpm for 45 seconds, and the viscosity was controlled at 5000-7000 mPa·s;

[0170] Under the dispersion condition, 2.281 kg of the fifth slurry and NMP (0.274 kg) were input into the slurry system 6, and the viscosity was adjusted by dispersing at 4000 rpm for 45 seconds, and the viscosity was controlled at 4000-7000 mPa·s;

[0171] Under the dispersion condition, 62.555 kg of the sixth slurry and NMP (0.137 kg) were input into the slurry system 7, and the viscosity was adjusted by dispersing at 3600 rpm for 45 seconds, and the viscosity was controlled at 3500-6500 mPa·s;

[0172] S5: The seventh slurry (62.692 kg) was input into the transfer stirring tank under stirring and dispersing conditions, and stirred for 30 min at a stirring speed of 5 rpm, a dispersing speed of 400 rpm, and a vacuum degree of ≤-98 kPa; the final slurry viscosity was controlled at 3500-6500 mpa·s, and the solid content was controlled at 67.5±1.5%.

[0173] Comparative Example 1

[0174] The difference from Example 1 is that a plurality of positive electrode materials are directly added using a traditional process, which includes the following steps:

[0175] S1: positive electrode material (positive electrode material 1 + positive electrode material 2): ​​binder: conductive agent: lithium supplement agent: conductive slurry: dispersant = mass ratio of 97.0:1.2:0.9:1:0.8:0.1, positive electrode material 1-NCM650728 (34.0kg), positive electrode material 2-LMFP (6.0kg), 5130 (0.227kg), lithium-rich ferric acid, LiTX300 (0.435kg) were added at the same time, and after high-speed mixing at 3200rpm / 4s, they were transported to a stirring tank, and NMP (7.799kg) was gradually added in a spraying form at a stirring speed of 15rpm and a dispersion speed of 1600rpm, and kneaded and stirred for 60min;

[0176] S2: MWCNTs conductive slurry -5% (6.598 kg), dispersant CGPS ​​313D8 (0.042 kg), and NMP (2.813 kg) were gradually and evenly added to the kneaded slurry system by spraying under stirring conditions, and then stirred for 130 min at a stirring speed of 25 rpm, a dispersion speed of 3200 rpm, and a vacuum degree of ≤-98 kPa;

[0177] S3: NMP (0.260 kg) was gradually and evenly added to the stirred slurry system by spraying, and the viscosity was adjusted at a stirring speed of 25 rpm, a dispersion speed of 3200 rpm, and a vacuum degree of ≤-98 kPa for 60 min; then, the bubbles were eliminated by stirring at a stirring speed of 5 rpm, a dispersion speed of 400 rpm, and a vacuum degree of ≤-98 kPa for 45 min; finally, the slurry viscosity was controlled at 3500-7500 mpa·s, and the solid content was controlled at 72.0±1.5%.

[0178] Comparative Example 2

[0179] The difference from Example 2 is that a plurality of positive electrode materials are directly added using a traditional process, including the following steps:

[0180] S1: positive electrode material (positive electrode material 1 + positive electrode material 2): ​​binder: conductive agent: lithium supplement agent: conductive slurry: dispersant = mass ratio of 96.30:1.40:1.25:1.5:0.9:0.15, positive electrode material 1-NCM650728 (12.0 kg), positive electrode material 2-LMFP (28.0 kg), 5130 (0.582 kg), lithium-rich ferric acid, LiTX300 (0.519 kg) were added, and after high-speed mixing at 3200 rpm / 4s, they were transported to a stirring tank, and NMP (9.138 kg) was gradually added in a spraying form at a stirring speed of 15 rpm and a dispersion speed of 1600 rpm, and kneaded and stirred for 60 minutes;

[0181] S2: MWCNTs conductive slurry -5% (7.477 kg), dispersant CGPS ​​313D8 (0.063 kg), and NMP (6.092 kg) were gradually and evenly added to the kneaded slurry system by spraying under stirring conditions, and then stirred for 130 min at a stirring speed of 25 rpm, a dispersion speed of 3200 rpm, and a vacuum degree of ≤-98 kPa;

[0182] S3: NMP (0.60 kg) was gradually and evenly added to the stirred slurry system by spraying, and the viscosity was adjusted at a stirring speed of 25 rpm, a dispersion speed of 3200 rpm, and a vacuum degree of ≤-98 kPa for 60 min; then, the bubbles were eliminated by stirring at a stirring speed of 5 rpm, a dispersion speed of 400 rpm, and a vacuum degree of ≤-98 kPa for 45 min; finally, the slurry viscosity was controlled at 3500-7500 mPa·s, and the solid content was controlled at 64.0±1.5%.

[0183] Comparative Example 3

[0184] The difference from Example 1 is that a variety of positive electrode materials are directly added using a traditional process, and S2-S7 are the same as Example 1, including the following steps:

[0185] S1: In the slurry 1 system, the mass ratio of positive electrode material (positive electrode material 1 + positive electrode material 2): ​​binder: conductive agent: lithium supplement agent: conductive slurry: dispersant = 97.0:1.2:0.9:1:0.8:0.1, positive electrode material 1-NCM650728 (34.0kg), positive electrode material 2-LMFP (6.0kg), 5130 (0.495), lithium-rich ferric acid, LiTX300 (0.371kg) were added, and after high-speed mixing at 3200rpm / 4s, they were transported to a stirring tank, and NMP (5.627kg) was gradually added in a spraying form at a stirring speed of 15rpm and a dispersion speed of 1600rpm, and kneading and stirring were performed for 60min;

[0186] S2: MWCNTs conductive slurry -5% (6.598 kg), dispersant CGPS ​​313D8 (0.042 kg), and NMP (2.813 kg) were gradually and evenly added to the kneaded slurry system by spraying under stirring conditions, and then stirred for 90 min at a stirring speed of 25 rpm, a dispersion speed of 3200 rpm, and a vacuum degree of ≤-98 kPa;

[0187] S3: input 55.90 kg of the first slurry and NMP (0.75 kg) into the slurry 3 system under dispersion conditions, disperse at 4500 rpm for 60 seconds, and control the viscosity at 6000-9000 mPa·s;

[0188] S4: input the third slurry 56.65 kg and NMP (0.188 kg) into the slurry 4 system under dispersion conditions, disperse at 4200 rpm for 45 seconds, and control the viscosity at 5000-8000 mPa·s; the ultrasonic condition is 20 Hz / 45 seconds;

[0189] Under the dispersion condition, the fourth slurry 56.838 kg and NMP (0.188 kg) were input into the slurry 5 system, and the viscosity was adjusted by dispersing at 4200 rpm for 45 seconds, and the viscosity was controlled at 5000-7000 mPa·s;

[0190] Under the dispersion condition, 57.026 kg of the fifth slurry and NMP (0.188 kg) were input into the slurry 6 system, and the viscosity was adjusted by dispersing at 4000 rpm for 45 seconds, and the viscosity was controlled at 4000-7000 mPa·s;

[0191] Under the dispersion condition, 57.214 kg of the sixth slurry and NMP (0.093 kg) were input into the slurry system 7, and the viscosity was adjusted by dispersing at 3600 rpm for 45 seconds, and the viscosity was controlled at 3500-6500 mPa·s;

[0192] S5: The seventh slurry (57.307 kg) was input into the transfer stirring tank under stirring and dispersing conditions, and stirred for 30 min at a stirring speed of 5 rpm, a dispersing speed of 400 rpm, and a vacuum degree of ≤-98 kPa; the final slurry viscosity was controlled at 3500-6500 mpa·s, and the solid content was controlled at 71.5±1.5%.

[0193] Experimental example

[0194] 1. Performance and morphology characterization test

[0195] The above Examples 1-4 were respectively analyzed using a viscometer, moisture tester, SEM, drying oven, and other related equipment familiar to technicians to test indicators such as sample SEM, solid content, viscosity and stability, membrane surface impedance, rate performance, and power-off cycles.

[0196] The SEM images of the ternary positive electrode materials prepared in Examples 1-4 and Comparative Examples 1-3 are shown in Figure 2 As shown in (a)-(d); the test results of slurry solid content, slurry stability and electrode membrane surface impedance are shown in Table 1 and Table 2;

[0197] Table 1 Test data of slurry solid content / viscosity etc. of Examples 1-4 and Comparative Examples 1-3

[0198]

[0199] Table 2 Slurry stability test data of Examples 1-4 and Comparative Examples 1-3

[0200]

[0201] Using the Blue Electric test system, the first charge and discharge specific capacity (see Figure 3 (a)-(d)) and 0.2C / 0.5C / 1.0C / 2.0C ((see Figure 4 (a)-(d)) rate discharge and 1C cycle performance tests are shown in Table 3 below.

[0202] Table 3 Test data of power-on performance indexes of Examples 1-4 and Comparative Examples 1-3

[0203]

[0204] It can be seen that the SEM characterization results of the electrodes in Examples 1-4 and Comparative Examples 1-3 show that the slurry dispersion morphology is more uniform and the membrane surface consistency is better through this process method. The membrane surface impedance test shows that the electrode membrane surface impedance is reduced by more than 50%; the slurry solid content test shows that the solid content is increased by ≥0.5%, which is beneficial to reduce the solvent usage and cost; the stability is improved by judging from the change trend of the static slurry viscosity; the buckling electrical performance test shows that the first discharge gram-to-gram capacity of the material is increased by about 1%, and the rate discharge performance is improved by about 2%; the overall homogenization time is about 3H, which is reduced by about 1h, which can improve the overall efficiency and production capacity; it can be seen that the inventive method has better comprehensive performance advantages.

[0205] 2. Electrical performance and safety performance test

[0206] The above-mentioned embodiment and comparative example slurries were prepared into PIE-116103322-61Ah soft-pack batteries (containing natural graphite for the negative electrode, 9+2+2 wet-process ceramic diaphragm, and HDGT's own electrolyte formula) according to the battery cell manufacturing process by methods well known to those skilled in the art. The electrode performance, electrical performance, and safety performance were tested. Low-temperature discharge, rate discharge, DCIR, normal temperature / high temperature 1C cycle, thermal stability DSC, and acupuncture safety performance tests were carried out in the voltage range of 2.75-4.40.

[0207] Table 4 Performance test results of Examples 1-2 and Comparative Examples 1-2

[0208]

[0209] It can be seen that the roller compaction density of Examples 1-2 and Comparative Examples 1-2 has increased year-on-year; the electrode peeling force has increased year-on-year; the electrode membrane surface impedance has decreased year-on-year; the low-temperature discharge and 2C rate discharge have increased by about 7%; the DCIR has decreased by about 60%; the normal temperature and high temperature cycle performance has increased by more than 50%; the DSC has increased by about 90°C; and the acupuncture safety performance has been effectively improved. Among them, Example 1-2 has a normal temperature cycle of 94.48% for 1513 weeks and 93.20% for 1522 weeks, and a high temperature cycle of 80.06% for 1416 weeks and 79.93% for 1383 weeks; Comparative Example 1-2 has a normal temperature cycle of 81.13% for 1611 weeks and 79.86% for 1561 weeks, and a high temperature cycle of 79.96% for 871 weeks and 80.67% for 821 weeks.

[0210] It can be seen that the stability of the composite slurry prepared by the present invention, the capacity utilization, rate, impedance, safety and cycle performance of the electrode and its battery are all improved.

[0211] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.

Claims

1. A slurrying process for a lithium-ion battery composite positive electrode slurry, characterized in that: The invention comprises a first slurry and a second slurry obtained by step-by-step dry high-speed mixing and step-by-step pulping, and a third slurry, a fourth slurry, a fifth slurry, a sixth slurry and a seventh slurry obtained by pulping by mixing and adjusting with a high-speed disperser and pipeline ultrasonic defoaming; The first slurry comprises a positive electrode material 1, a binder 1, a conductive agent 1, a lithium supplement agent 1, a conductive slurry 1 and a solvent; the second slurry comprises a positive electrode material 2, a binder 2, a conductive agent 2, a lithium supplement agent 2, a conductive slurry 2 and a solvent; the third slurry comprises the first slurry, the second slurry and a solvent; the fourth / fifth / sixth / seventh slurry comprises the third slurry and a solvent; The positive electrode material 1 and the positive electrode material 2 are positive electrode raw materials of different structural types and particle sizes; the binder 1 and the binder 2 can be the same or different; the conductive agent 1 and the conductive agent 2 can be the same or different; the lithium supplement agent 1 and the lithium supplement agent 2 can be the same or different; the conductive paste 1 and the conductive paste 2 can be the same or different; The first slurry and the second slurry may further include a dispersant.

2. A slurrying process for a lithium-ion battery composite positive electrode slurry as claimed in claim 1, characterized in that: The steps include: S1: Under high-speed mixing and stirring conditions, the positive electrode material, the conductive agent, the lithium supplement agent and the binder are continuously added in proportion to the first slurry and the second slurry preparation system respectively, and the mixture is transported to the stirring tank after high-speed mixing in the high-speed mixer, and part of the solvent is continuously added in proportion in the form of spraying for stirring and kneading for a certain time; S2: Under stirring and dispersing conditions, part of the solvent and all of the conductive slurry and dispersant are continuously added in a spraying form according to the proportion. After the materials are added, they are stirred at high speed for a certain period of time under vacuum conditions to complete the primary preparation of the first slurry and the second slurry respectively; S3: under stirring and dispersing conditions, the first slurry and the second slurry are transported to the high-speed stirring and dispersing machine system of the third slurry according to the designed ratio, and part of the solvent is added to perform high-speed dispersion for a certain period of time to obtain the third slurry, and then the viscosity is monitored and controlled by an online viscosity tester, and then the bubbles are automatically transported to the fourth slurry system in the next step by ultrasonic elimination of the pipeline; S4: under stirring and dispersing conditions, the third slurry is transported to the high-speed stirring and dispersing machine system of the fourth slurry through a pipeline, and part of the solvent is added for high-speed dispersion to obtain the fourth slurry, and then the viscosity is characterized by an online viscosity tester, and then the bubbles are eliminated by ultrasonic pipeline and automatically transported to the next slurry system; that is, the fourth / 5th / 6th / 7th slurries are respectively prepared by repeating the third slurry to the fourth slurry steps, and the amount of solvent added to the fourth slurry to the seventh slurry can be automatically calculated and added by proportionally controlling the flow rate according to the online slurry viscosity feedback data; S5: under stirring conditions, conveying the seventh slurry to the transfer stirring tank, and after the addition is completed, continuing to stir for a certain period of time under a certain vacuum degree to prepare the lithium-ion battery positive electrode composite slurry.

3. The homogenization process of a lithium-ion battery composite positive electrode slurry according to claim 2, further characterized in that: The first slurry and the second slurry are slurries prepared by combining different types of raw materials and formulation systems, and the positive electrode material, conductive agent, lithium supplement agent and binder are all in powder form; The weight ratio of positive electrode material 1: binder 1: conductive agent 1: lithium supplement agent 1: conductive paste 1: dispersant 1 in the first slurry system = (88.0-99.0): (0.8-2.0): (0.1-5.0): (0.1-4.0) (0.02-1.8): (0.01-0.5); The weight ratio of positive electrode material 2: binder 2: conductive agent 2: lithium supplement agent 2: conductive paste 2: dispersant 2 in the second slurry system = (85.0-98.5): (1.2-4.0): (0.2-8.0): (0.1-5.0): (0.01-2.0): (0.01--0.5); The ratio of positive electrode material 1 to positive electrode material 2 in the first slurry and the second slurry system contained in the third slurry is (5-92):(8-95).

4. The homogenization process of a lithium-ion battery composite positive electrode slurry according to claim 2, further characterized in that: The positive electrode material 1 is composed of one or more of a layered micron-sized material, wherein the positive electrode material 1 includes a combination of one or more of NCM, NCA, NCMA, LCO, LMO, NNFC, NNFM, and NNFCM; The positive electrode material 2 is composed of one or more polyanionic nano-scale or submicron-scale materials, and the positive electrode material 2 includes a combination of one or more of LFP, LMFP, LVPF, NVPF, and NFP; The binder 1 or the binder 2 is a combination of one or more of polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA) or acrylonitrile multi-polymer; The solvent includes any one or more of N-methylpyrrolidone, dimethylacetamide or dimethyl sulfoxide; The conductive agent 1 and the conductive agent 2 are a combination of one or more of carbon black, graphite powder, carbon fiber, metal oxide conductive agent, and fast ion conductive agent materials; The lithium supplement agent 1 and the lithium supplement agent 2 are a combination of one or more of lithium-rich nickel acid, lithium-rich cobalt acid, lithium-rich ferric acid, Li2S / Co, LiF / Co, Li2O / Co, Li2O, Li2O2, Li3N, and Li2S powder materials; The conductive paste 1 and the conductive paste 2 are conductive pastes obtained by compounding carbon nanotubes / graphene with a conductive agent, wherein the conductive agent is one of the powder materials of carbon black, graphite powder, carbon fiber, metal oxide conductive agent, and fast ion conductive agent.

5. The homogenization process of a lithium-ion battery composite positive electrode slurry according to claim 2, further characterized in that: The carbon black is a combination of one or more of conductive carbon black SP, Super P-Li, KB, and AB: The graphite powder is a combination of one or more of KS-6, KS-15, SFG-6, and SO; The carbon fiber conductive agent is a combination of one or more of nanocarbon fibers (VGCF), carbon nanotubes (SWNTs, MWNTs) and carbon fibers (GN); The metal oxide conductive agent is a combination of one or more of ZnO, SnO2, Sb2O3, In2O3, TiO2, and ATO powder; The fast ion conductor is a combination of one or more of LATP, LAZP, LLZP, LLZO, LLZTO, and LLTO solid electrolyte fast ion conductor materials; or a combination of one or more of Li3YCl6, Li3Y(Br3Cl3), Li3ErCI6, Li3InCI6, Li3ErBr6, Li3ErI, Li3InBr6, and Li3InI6 halide fast ion conductor materials; or Beta alumina, Nasicon (Na3Zr2Si2PO 12 ) one or a combination of sodium ion fast ion conductor materials; The graphene conductive agent is a combination of one or more of graphene powder, graphene film, graphene / carbon black composite conductive agent, and graphene / carbon nanotube composite conductive agent; The dispersant is one or two or more of an amphoteric dispersant, a polymer copolymer dispersant, a PVP dispersant, a polyether dispersant, a polyester dispersant, a carboxylic acid dispersant, and a sulfonic acid dispersant.

6. The homogenization process of a lithium-ion battery composite positive electrode slurry according to claim 2, further characterized in that: By weight, the solvent ratio in step S1 accounts for 55-65% of the total solvent ratio; the solvent ratio in step S2 accounts for 20-35% of the total solvent ratio; the solvent ratio in step S3 accounts for 6-10% of the total solvent ratio; the solvent ratio of the 4th slurry system in step S4 accounts for 1-2% of the total solvent ratio, and the solvent ratio of the 5th / 6th / 7th slurry system in step S4 is adjusted to adjust the viscosity according to 1-2% of the total solvent ratio.

7. The homogenization process of a lithium-ion battery composite positive electrode slurry according to claim 2, further characterized in that: In the step S1, the stirring speed is 10 to 30 rpm; the dispersion speed is 1200 to 2500 rpm; The kneading time is 30 to 60 minutes, preferably 45 to 60 minutes; The dry mixing in step S1 adopts a pipeline high-speed mixer; the speed of the high-speed mixer in step S1 is 2000-5000 rpm, and the mixing time is 1-10S; In step S2, the stirring speed is 15 to 35 rpm; the dispersion speed is 1500 to 3200 rpm; The stirring time is 60 to 120 minutes, preferably 60 to 90 minutes; In step S3, the slurry is dispersed at a high speed of 3000 to 8000 rpm; The slurry high-speed dispersion time is 10 to 90 seconds; In step S4, the slurry high-speed dispersion speed is 3000-8000 rpm; the slurry high-speed dispersion time is 10-60 s; In the steps S3 and S4, a slurry disperser is used for high-speed dispersion; In steps S3 and S4, ultrasonic defoaming of pipeline slurry is performed, and the ultrasonic frequency can be 10 to 35 Hz and the time is 10 to 90 seconds; In step S5, the stirring speed is 2 to 10 rpm; the dispersion speed is 100 to 600 rpm; The stirring time is 30 to 60 minutes, preferably 30 to 45 minutes.

8. The homogenization process of a lithium-ion battery composite positive electrode slurry according to claim 2, further characterized in that: In step S2, the first slurry viscosity is controlled within a range of 12000 to 15000 mpa·s, and the second slurry viscosity is controlled within a range of 13000 to 16000 mpa·s; In step S3, the viscosity of the third slurry is controlled in a range of 6000 to 10000 mpa·s; In the step, the viscosity control range of the slurry in the fourth step can be 5000-9000 mpa·s, the viscosity control range of the slurry in the fifth step can be 4000-8000 mpa·s, the viscosity control range of the slurry in the sixth step can be 4000-7500 mpa·s; the viscosity control range of the slurry in the seventh step can be 3500-7500 mpa·s; In step S5, the viscosity of the slurry is controlled in the range of 3000 to 7500 mpa·s; In the stirring tank, the vacuum degree is ≤-98 kPa, and the internal temperature of the stirring tank is ≤50°C.

9. A composite positive electrode slurry for a lithium ion battery prepared by the homogenization process of the composite positive electrode slurry for a lithium ion battery according to any one of claims 1 to 8.

10. An application of a lithium-ion battery composite positive electrode slurry prepared by the preparation method according to any one of items 1 to 8, characterized in that: A secondary battery positive electrode sheet prepared by the positive electrode slurry obtained by any one of the homogenization processes of claims 1-8, or the use of the electrode prepared based on the homogenization process in a secondary battery, or a secondary battery thereof.

Citation Information

Patent Citations

  • Method for preparing uniform slurry for positive electrode of lithium ion battery

    CN107910546A

  • Lithium ion battery positive electrode slurry, homogenizing method and application thereof

    CN112635715A

  • Positive electrode homogenization method, positive electrode slurry and its application

    CN114156431B

  • Positive electrode slurry, preparation method thereof and positive electrode plate

    CN115832172A

  • Homogenizing method of battery positive electrode material

    CN116532017A